Structure and Meaning in the Poem Kamu Tidak Istimewa: A Structural Analysis of Natasya Risky’s Work - Siti Munfaizzah; Siti Nur Afifatul Hikmah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the structural elements and meaning of the poem “Kamu Tidak Istimewa” by Natasya Riski through a structural approach. The research is based on the consideration that structural analysis in contemporary Indonesian poetry, particularly in exploring the relationship between form and meaning, remains limited. Therefore, this study aims to describe the physical structure and inner structure of the poem and to explain how these elements contribute to the construction of meaning. This research employs a qualitative descriptive method using textual analysis techniques, which involve identifying, classifying, and interpreting the structural elements of the poem. The physical structure analyzed includes diction, imagery, concrete words, figurative language, rhyme, and typography, while the inner structure consists of theme, feeling, tone, and message. The findings indicate that the poem utilizes reflective and evaluative diction, supported by the repetition of imperative expressions such as “Berbahagialah,” as well as contrasting imagery that presents differences between comfort and suffering. These structural elements work together to illustrate the speaker’s shift from a self-centered perspective toward a broader awareness of human experience. The use of concrete words and figurative language strengthens the emotional expression, while the free typographical form supports the reflective flow of the poem. This study demonstrates that repetition, imperative diction, and contrasting imagery function as structural devices that construct the poem’s critique of human egocentrism. The results of this study are expected to contribute to the development of literary studies, particularly in providing a more comprehensive understanding of structural analysis in contemporary Indonesian poetry.